EVALUASI PEMANFAATAN FITUR PERPANJANGAN MANDIRI SLIMS MENGGUNAKAN METODE DEBUGGING - Andi Saputra (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2021)
Introduction. The Self-service Extension feature is one of the innovations developed by SLiMS community since 2015. Its function is to facilitate users in extending the loan period of borrowed books by themselves.  Purpose and Method. This study aims to evaluate the performance of the Self-service Extension feature using debugging(error tracking) method by connecting symptoms and causes of errors.  Results and Discussion. The results found several weaknesses.This module cannot run properly if the number of loan extensions is set more than once, and information on the amount of fines displayed does not count Sundays as holidays, so the penalty rate displayed exceeds the amount that should be paid. From this study it can be concludedthat the use of the debugging method is quite effective in tracking errors (bugs) on modules with simple program code, such as the Self-service Extension feature. After repairs, the feature can run as it should according to the rules set by its parent application, SLiMS. Its function can be maximized in helping facilitate library users to extend the period of borrowed books online, as well as to see information on the amount of fines to be paid.